Intensification of Photobiocatalytic Decarboxylation of Fatty Acids for the Production of Biodiesel. Issue 4 (2nd February 2021) - Duong, Hong T.; Wu, Yinqi; Sutor, Alexander; Burek, Bastien O.; Hollmann, Frank; Bloh, Jonathan Z.
Abstract: Light‐driven biocatalytic processes are notoriously hampered by poor penetration of light into the turbid reaction media. In this study, wirelessly powered light‐emitting diodes are found to represent an efficient and scalable approach for process intensification of the photobiosynthetic production of diesel alkanes from renewable fatty acids. Abstract : Setting light to fatty acids : The photodecarboxylation of fatty acids to alkanes presents an intriguing way of producing biodiesel. Using delocalized wirelessly powered internal illumination leads to a reaction that is more efficient, dramatically accelerated, and readily scalable, clearly pointing towards industrial implementation.